META-ANALYSIS: DEVELOPMENT OF TEACHING MATERIALS AND LEARNING MEDIA ON MOLECULAR GENETICS MATERIALS IN SMA - Meitafia, Elda Meitafia; Hamidah, Afreni; Siburian, Jodion; Murni, Pinta (Universitas Lancang Kuning, 2024)
Molecular genetics material is considered difficult and abstract, so it often causes misconceptions in understanding the material. The use of effective teaching materials and learning media can support learning on molecular genetics material. This study aims to determine the effectiveness of using teaching materials and learning media to improve students' understanding of molecular genetics material in high school. This research uses a qualitative descriptive approach with the systematic literature review (SLR) method. Data sources were obtained through a literature review by reviewing various publications from previous journals obtained from Google Scholar and Publish or Perish 8 which areaccredited at least sinta 4. The results show that teaching materials in the form of E-LKPD are more effective to use, as seen from the higher average results of validation and feasibility testing, namely 4.19 and 96.85%. Learning media that is more effective to use is interactive multimedia in the form of educational games. This can be seen from the higher pretest and posttest results compared to other media, namely the pretestresults of 9.7% and post-test results of 93.5%. The pretest and posttest results received an increase of 83.8%. The use of effective and interesting teaching materials and learning media can improve the understanding of molecular genetics material in high school.